Dhol : drummers, identities, and modern Punjab - Schreffler, Gibb (University of Illinois Press, 2021)
"In the early twenty-first century, the Punjab region's traditional drummers, dholis, were experiencing "the toughest time ever." Concurrently, their instrument, the iconic barrel drum dhol, was experiencing unprecedented global popularity. This book uncovers why, notwithstanding the emblematic status of dhol for Punjabis, the dholis' local communities are facing existential crisis. The pursuit of a national identity-which aids in political representation and maintaining historical consciousness during change-has led modern Punjabis to make particular economic, social, and artistic choices. A casualty of this pursuit has been the disenfranchisement of dholis, who do not find representation despite the symbolic import of dhol to that national identity. Through the example of dhol's subtle appropriation, the book argues that the empowerment gained by bolstering Punjabi identity in the global arena works at the expense of people on Punjabi society's margins. At its core are the hereditary-professional drummers who, while members of society's low-status "outcaste" population, created and maintained dhol traditions over centuries. Exacerbated by a cultural nationalist discourse that downplays ethnic diversity, their subaltern ethnic identities have been rendered invisible. Recognizing their diverse ethnic affiliations, however, is only the first step toward hearing hitherto absent perspectives of individual musicians. As a work of advocacy, this book draws on two decades of ethnography of Indian, Pakistani, and diasporic Punjabi drummers to center their experiences in the story of modern Punjab"--